The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique

Blanches et Noires : histoire(s) des Américaines au XIXe siècle - Lehuu, Isabelle (Cahiers de l'IREF, 2011)
«Les chapitres qui suivent mettent en lumière tant la parole des femmes que le discours sur les femmes, les actions et les représentations. Ils explorent la réalité quotidienne de femmes ordinaires du XIXe, jeunes et moins jeunes, mariées et célibataires, blanches et noires, au Nord comme au Sud, qui sont restées silencieuses, souvent dans l’ombre d’un mari, d’un père ou d’un maître. Leurs témoignages, les mots qu’elles ont laissés dans les sources publiques et privées, les gestes qu’elles ont posés aussi bien dans le cadre de leurs relations affectives qu’au sein de leur exploitation familiale, leur réseau social, leur travail, leur église, leur communauté urbaine ou villageoise, leur région, sont autant d’indices à décoder pour dresser un portrait nuancé et documenter la condition des femmes aux États-Unis dans toute sa diversité sociale et culturelle.»
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; black feminism; cours; discipline; esclavagisme; femmes* blanches; femmes* noires; féminisme afroaméricain; féminismes noirs; his4443; histoire; histoire des femmes*; intersectionnalité; justice sociale; militance; mouvement aboitionnisme; philosophie politique; premier cycle; privilèges; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis; états-unis (sud); études féministes